Treatment of large bone defects with a novel biological transport disc in non-vascular transport distraction osteogenesis. Issue 5 (May 2016) - Zeng, J.J.; Guo, P.; Zhou, N.; Xie, Q.T.; Liao, F.C.
Abstract: The aim of this study was to investigate a potential novel biological transport disc that avoids secondary injury to the body and facilitates bone healing. Twenty-seven dogs were divided randomly into three groups: group A were treated with human bone morphogenetic protein 2 (BMP-2) modified bone mesenchymal stem cell (BMSC) sheets combined with freeze-dried bone allograft as biological transport disc; group B were treated with BMSC sheets combined with freeze-dried bone allograft as transport disc (control); and group C were treated with direct extension only (blank). There were nine dogs in each group. Non-vascular transport distraction osteogenesis was performed in groups A and B to repair the mandibular bone defects, and in group C only mandibular truncation surgery was performed. The regeneration of bone was evaluated through X-ray, haematoxylin and eosin assay, and immunohistochemistry. After 2, 4, and 8 weeks of distraction, new bone density values in group A were 49.00 ± 1.16, 66.63 ± 2.62, and 72.78 ± 2.67, respectively, and these were significantly different to values in groups B ( P = 0.0005, P = 0.0004, P = 0.0012) and C ( P < 0.0005, P = 0.0001, P = 0.0003). The average grey value for BMP-2 expression in group A after 4 weeks of distraction was 195.63 ± 4.45, which was significantly different when compared to groups B ( P = 0.0022) and C ( P = 0.0006). This novel biological transport disc represents an effective non-secondary injury method to enhance new bone formation in non-vascular transport distraction osteogenesis.